A hybrid approach for modelling the acoustic properties of recycled fibre mixtures for automotive applications. (November 2021) - Santoni, Andrea; Bonfiglio, Paolo; Magnani, Aurora; Marescotti, Cristina; Pompoli, Francesco; Fausti, Patrizio
Abstract: The acoustic modelling of fibrous materials is fundamental for the design of a sound-absorbing acoustic treatment. Several analytical formulas have been proposed to calculate the acoustic performance of materials made of fibres with a homogeneous diameter and a mono, bi, or three-dimensional distribution, while only a few studies have been carried out on materials made up of a mixture of fibres with non–homogeneous diameter. Fibrous materials for automotive applications, developed both for acoustic and thermal applications, are commonly obtained by moulding mixtures of recycled fibres of different nature, bonded together and compacted with a wide range of variability in density and thickness. The acoustic modelling of the mixtures is thus relevant for the simulation of the performance of the final component. The main goal of the study was to determine the physical properties of a given mixture of fibres to compute its acoustic performance, based on the knowledge of the characteristic of each kind of fibre in the blend composition. A homogenisation process is proposed to determine the effective density and radius of a given mixture according to its composition and the characteristics of each kind of fibre. The normal incidence sound absorption coefficient of the investigated mixtures was computed according to the Johnson-Champoux-Allard-Lafarge (JCAL) model, by using the physical parameters, analytically computed from the effective properties of the mixture, as input data. The reliability of the approach was validated by comparing the computed results with the experimental airflow resistivity and the normal incidence sound absorption coefficient measured for five different fibre mixtures, at different compression rates.